The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40991-017-0014-z
|View full text |Cite
|
Sign up to set email alerts
|

Renewing and improving the business model toward sustainability in theory and practice

Abstract: The paper aims to analyse and discuss the evolution towards a sustainable business model and to focus on the motivations and the implications on the mission, the governance and the accountability of companies. Moreover, the theoretical framework of values-based, ethical and sustainable leadership has been used as interpretative key for the case-study analysis. After presenting the literature review, the second part of the work is based on the inductive approach applied to the analysis of the experience of an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…In this study, transformational leadership was found to be positively related to sustainability. This result was consistent with previous literature which indicated that one of the attributes of sustainability today is the role of transformational leadership (Baldo & Baldarelli, 2017;Chan & Chan, 2005;Feyerherm & Parker, 2015;Meng et al, 2015;Muralidharan & Pathak, 2018;Müller & Judgev, 2012;Muller & Turner, 2010;Tabassi et al, 2016;Yang et al, 2011). Therefore, transformational leadership is a significant variable for promoting sustainability in property development in Malaysia because it is essential to sustainable achievement where management possess the necessary leadership competencies, skills and knowledge to be able to achieve sustainability in property development.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, transformational leadership was found to be positively related to sustainability. This result was consistent with previous literature which indicated that one of the attributes of sustainability today is the role of transformational leadership (Baldo & Baldarelli, 2017;Chan & Chan, 2005;Feyerherm & Parker, 2015;Meng et al, 2015;Muralidharan & Pathak, 2018;Müller & Judgev, 2012;Muller & Turner, 2010;Tabassi et al, 2016;Yang et al, 2011). Therefore, transformational leadership is a significant variable for promoting sustainability in property development in Malaysia because it is essential to sustainable achievement where management possess the necessary leadership competencies, skills and knowledge to be able to achieve sustainability in property development.…”
Section: Discussionsupporting
confidence: 90%
“…This feature is part of the company's identity and forges its business model that is driven toward strong sustainability (Ayres et al 1998). Notably, it derives from core values that have been inherited from the entrepreneurial family through generations (Looser and Wehrmeyer 2015;Del Baldo and Baldarelli 2017). Moreover, it is tied to its social capital, that is the systems of values, norms and behaviors that the entrepreneur ant the top management share with the stakeholders (Del Baldo, 2014).…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…The need for developing SBMs and their implementation in practice has been pointed out by several authors (Visser 2011;Dean and McMullen 2007;Hall et al 2010) who consider them fundamental for trigger more outward-oriented conceptions of CSR (corporate social responsibility) and sustainability (Schaltegger et al 2016;Looser and Wehrmeyer 2015;Del Baldo 2012;Del Baldo and Baldarelli 2017) fashioned through dynamic and continuous interactions between individuals and groups inside and outside companies (Thompson et al 2015). The elements that contribute to driving a transformation toward SMBs requires the building of networks and collaborative practices for learning and action around a new shared vision and generate social value creation Mair 2005, 2006;Johnson 2010;Patzelt and Shepherd 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…But now, it is a time for every responsible citizen and the company must contribute to the country cause [9,10]. The business these days is not only related to the profit maximization of the company and shareholders but also responsible to do something for the stakeholders and community people [2,11]. The objective of this study is to study the consciousness of customers of a different company (Standard Chartered Bank, Ncell, Asian Paints, Yeti Airlines and Dabur Nepal) on awareness of corporate social responsibility related activities of different companies for building brands in Nepal.…”
Section: Introductionmentioning
confidence: 99%